Improvement Strategy Knowledge and Skills of Daily Makeup for Household Women and Working Women - Widowati, Trisnani; Nurhayati, Ifa; Agustin, Eny Widhia; Suryani, Parsih Wulan; Febriani, Berliana Dwi; Wildaningtyas, Eka Rosiana (Universitas Negeri Semarang, 2023)
Semarang city has 16 sub-districts, of which Gunungpati sub-district is Wrong One among them. Subdistrict This location not enough more from 30 kilometers from Semarang toward north. Subdistrict Mount Pati Alone own number of villages 16 fruit And village Patemon is Wrong one of them. Inhabitant Which stay in village The majority of housewives in RW 07 are Aanita office workers, lecturers And nurse. One of the characteristics of modern women today this is a woman who does personal care and makeup in daily activities. Applying makeup for women office workers useful for supporting a more visible appearance beautiful and can increase women 's self-confidence at work. Woman Which Work office often meet with clients, this of course makes women in the profession as an office worker requires knowledge of daily makeup as supporting their appearance so that they are more confident when meeting clients. Constraint Which faced para Mother House the stairs especially Mother worker in village Patemon RW 07 The first is a lack of knowledge about daily make-up according to type facial skin and face shape, both require training on daily make-up that is appropriate to the face shape and skin type for outdoor activities. office, and to add ability in skills make-up face Which can used Also in add income family.